Sahoo's handbook on service matters for IAS, IPS and IFS 2008 - Sahoo, D. C. (Bhubaneswar, 2008)
This handbook is about the regulation of cadres, pay scale, appointments, seniority, promotion, performance appraisal report, etc.
Keywords: Service matters